Advance selling of new products to strategic consumers on flash sale platforms. Issue 3 (4th May 2018) - Zhang, Mingyang; Cheng, T.C.E.; Du, Jie
ABSTRACT: Flash sale (FS) is a new business model that offers discounted products in limited numbers over a short period. In this paper we discuss the impact of strategic consumers on advance selling (AS) of new products on FS platforms. We first study the impact of strategic consumers on competing retailers adopting AS to sell a homogeneous new product. And find that the retailers' AS profits and inventory quantities decrease with the strategic customers' valuation and valuation decreasing rate. Then we analyse whether FS can mitigate the impact of strategic customers on retailers adopting AS for new products. We consider a newsvendor model involving only one retailer adopting AS to sell a new product. We derive the results by comparing this model with two counterpart models, namely the classical newsvendor model with no strategic customers and a newsvendor model with strategic customers where the retailer does not use FS under AS.